2015
DOI: 10.1063/1.4922864
|View full text |Cite
|
Sign up to set email alerts
|

Shape effects on dynamics of inertia-free spheroids in wall turbulence

Abstract: The rotational motion of inertia-free spheroids has been studied in a numerically simulated turbulent channel flow. Although inertia-free spheroids were translated as tracers with the flow, neither the disk-like nor the rod-like particles adapted to the fluid rotation. The flattest disks preferentially aligned their symmetry axes normal to the wall, whereas the longest rods were parallel with the wall. The shape-dependence of the particle orientations carried over to the particle rotation such that the mean sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 24 publications
5
18
0
Order By: Relevance
“…Recently Voth [33] argued that a weakly-inertial oblate spheroid aligned near the wall-normal direction will spend a long time in this orientation before tumbling. Challabotla et al [34] similarly observed that prolate tracers with their symmetry axis almost aligned in the streamwise direction rarely tumble and the observed orientation and rotation of tracer spheroids in the viscous sub-layer was qualitatively consistent with spheroids in Jeffery orbits in linear shear flow. Thus we conclude that the weak tumbling and spinning for inertia-free spheroids with high aspect ratio can be attributed to Jeffery-like orbiting.…”
mentioning
confidence: 56%
“…Recently Voth [33] argued that a weakly-inertial oblate spheroid aligned near the wall-normal direction will spend a long time in this orientation before tumbling. Challabotla et al [34] similarly observed that prolate tracers with their symmetry axis almost aligned in the streamwise direction rarely tumble and the observed orientation and rotation of tracer spheroids in the viscous sub-layer was qualitatively consistent with spheroids in Jeffery orbits in linear shear flow. Thus we conclude that the weak tumbling and spinning for inertia-free spheroids with high aspect ratio can be attributed to Jeffery-like orbiting.…”
mentioning
confidence: 56%
“…Turbulent channel flow of non-spherical particles has been investigated by several authors (Zhang et al 2001;Mortensen et al 2008;Marchioli et al 2010;Challabotla et al 2015a), with focus on the particle dynamics. Challabotla et al (2015b) investigated the rotational motion of inertia-free spheroids in turbulent channel flow using the equations by Jeffery (1922) for the particle rotation. These authors showed that oblate spheroids preferentially align their symmetry axes normal to the wall, whereas prolates are preferentially parallel to the wall.…”
Section: Introductionmentioning
confidence: 99%
“…A natural question to ask is how the presence of walls affects the alignment behaviour of slender rods? Zhao & Andersson (2016) found that elongated rods in a turbulent channel flow align preferentially with the Lagrangian stretching direction, but that the orientation and rotation behaviours appear to depend quite sensitively upon the aspect ratio near the wall (Challabotla, Zhao & Andersson 2015; Zhao et al 2015). Several authors have analysed how the orientation of slender rods aligns with the laboratory-fixed basis of a turbulent channel flow.…”
Section: Introductionmentioning
confidence: 99%
“…We study how the distribution of relative angles depends on the particle aspect ratio and on the distance of the particle from the channel wall. Our numerical studies employ DNS of a turbulent channel flow with a friction Reynolds number (Challabotla et al 2015).…”
Section: Introductionmentioning
confidence: 99%